High explosives, propellants, pyrotechnics - Koch, Ernst-Christian (De Gruyter, 2021)
This dictionary contains 739 entries with about 1400 references to the primary literature. Details on the composition, performance, sensitivity and other pertinent properties of Energetic Materials such as High Explosives, Propellants, Pyrotechnics, as well as important ingredients such as Oxidizers, Fuels, Binders, and Modifiers are given and presented partly in over 180 tables with more than 240 structural formulas . In detail the dictionary gives elaborate descriptions of 460 Chemical Substances 170 Pyrotechnic Compositions 360 High Explosive and Propellant Formulations In addition, the basic physical and thermochemical properties of 435 pure substances (elements & compounds) typically occuring as ingredients or reaction products are given too. 150 Figures, schemes and diagrams explain Applications, Test methods, Scientific facilities, and finally Individuals closely tied with the development and investigation of Energetic Materials. The book is intended for readers with a technical or scientific background, active in governmental agencies, research institutes, trade and industry, concerned with the procurement, development, manufacture, investigation and use of Energetic Materials, such as High Explosives, Propellants, Pyrotechnics, Fireworks and Ammunition. The book serves both as a daily reference for the experienced as well as an introduction for the newcomer to the field.
Includes index.
Keywords: Explosives -- Encyclopedias.; Propellants -- Encyclopedias.; elektronické knihy; electronic books